İslam’daki ruh ve nefis telakkisinin eğitime tesirleri - Sezgin, Osman (My University, 1985)
unknown
Keywords: Akıl; Akıl - İslâm felsefesi; Araştırma; Dini yönler; Education; Eğitim; Eğitime etki eden faktörler; Felsefe, İslami; Human; Human breath --Education; Islam; Islamic philosophy; Islamic religious; İnsan; İnsan nefsi; İslam; İslam dini; İslam felsefesi; Koran; Nafs; Nefs; Nefs - Kur’an; PDR; Philosophy, Islamic; Reason; Religious aspects; Research; Ruh; Soul